Efficacy of Plant‐Derived Antimicrobials as Antimicrobial Wash Treatments for Reducing Enterohemorrhagic Escherichia Coli O157:H7 on Apples. Issue 9 (23rd August 2013) - Baskaran, Sangeetha Ananda; Upadhyay, Abhinav; Kollanoor‐Johny, Anup; Upadhyaya, Indu; Mooyottu, Shankumar; Roshni Amalaradjou, Mary Anne; Schreiber, David; Venkitanarayanan, Kumar
Abstract: This study investigated the efficacy of 3 GRAS‐status, plant‐derived antimicrobials (PDAs), trans ‐cinnamaldehyde (TC), carvacrol (CR), and β‐resorcylic acid (BR) applied as an antimicrobial wash for killing Escherichia coli O157:H7 on apples. "Red delicious" apples inoculated with a 5 strain mixture of E. coli O157:H7 were subjected to washing in sterile deionized water containing 0% PDA (control), 0.15% TC, 0.35% TC, 0.15% CR, 0.30% CR, 0.5% BR, or 1% BR for 1, 3, and 5 min at 23 °C in the presence and absence of 1% soil, and surviving pathogen populations on apples were enumerated at each specified time. All PDAs were more effective in reducing E. coli O157:H7 compared to the water wash treatment ( P < 0.05) and reduced the pathogen by 4‐ to 5‐log CFU/apple in 5 min. Chlorine (1%) was the most effective treatment reducing the pathogen on apples to undetectable levels in 1 min ( P < 0.05). Moreover, the antimicrobial effect of CR and BR was not affected by the presence of soil, whereas the efficacy of TC and BR was decreased in the presence of soil. Further, no bacteria were detected in the wash solution containing CR and BR; however, E. coli O157:H7 was recovered in the control wash water and treatment solutions containing TC and chlorine, in the presence of 1% soil ( P < 0.05). Results suggest that the aforementioned PDAs, especially CR and BR could be used effectively to kill E. coli O157:H7 on apples when used as a wash treatment. Studies on the sensory and quality characteristics of apples treated with PDAs are needed before recommending their usage.